Pattern of Uptake of Maternal Health Services in a Rural Community in Nigeria (2010)
The care and assistance that women receive during pregnancy and delivery are key underlying factors affecting the maternal mortality ratio. This study examines the pattern of use of maternal health services in a rural community in Ibadan, Nigeria. in a cross-sectional study, a questionnaire was administered to collect data from 150 women, who had been pregnant and given birth at least once before, of childbearing age. Educational status of the women was low and they used more of the services from informal settings. Availability of the health facility was the main factor that influenced the use of maternal health services. The major barriers to the use of formal services were unavailability of health workers at the health institutions, attitude of the workers, as well as cost of purchase of various items. Educational status had significant association with use of various maternal health services. This study recommends that maternal health services should be made accessible in the rural communities and education of women should be re-emphasized.